Impact of Drudgery-Reducing Agricultural Tools on Women Farmers in Karnali Province, Nepal - Acharya, Rudra Prasad (Karnali Outlook: Knowledge Across Disciplines, 2026)
This study examines the impact of the Drudgery Reduction Equipment and Tools Support (DRETS) initiative implemented under the Agricultural Sector Development Program (ASDP) on women farmers in Karnali Province, Nepal. Using a mixed-methods approach, the research draws on quantitative and qualitative data collected from 618 households across five districts to assess changes in labor use, productivity, income, and well-being following the adoption of drudgery-reducing agricultural tools. A production function framework was applied to analyze how capital inputs in the form of tools and equipment interacted with labor and material inputs to influence agricultural outcomes. The study finds that the introduction of appropriate, women-friendly tools significantly reduced the physical burden and time intensity of agricultural work without compromising productivity. Instead, farming efficiency improved, enabling women to maintain or increase agricultural output while relying on less manual labor. Reduced drudgery contributed to better health, lower fatigue, and improved time management among women farmers, allowing some to engage in additional productive or income-generating activities. The results indicate that gains in agricultural income were driven primarily by efficiency improvements associated with technology adoption rather than increased labor effort. Despite these positive outcomes, the study also identifies persistent constraints related to the affordability of equipment, limited access to repair and maintenance services, and prevailing gender norms that restrict women’s full control over agricultural technologies. The study concludes that targeted mechanization is an effective strategy for reducing women’s drudgery and enhancing economic empowerment in marginal regions, but its long-term impact depends on complementary measures addressing access, affordability, and gender-related barriers.